2005
DOI: 10.1302/0301-620x.87b7.15774
|View full text |Cite
|
Sign up to set email alerts
|

Immobilisation of forearm fractures in children

Abstract: Redisplacement of unstable forearm fractures in plaster is common and may be the result of a number of factors. Little attention has been paid to the influence of immobilisation with the elbow extended versus flexed. We prospectively treated 111 consecutive children from two centres with closed forearm fractures by closed reduction and casting with the elbow either extended (60) in China or flexed (51) in Israel. We compared the outcome of the two groups. There was no statistically significant difference in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 5 publications
(8 reference statements)
0
16
1
1
Order By: Relevance
“…Previous studies have found a re-displacement rate of 7–27% in non-operatively treated forearm fractures, whereas we found a rate of 34% (Monga et al 2010, Kay et al 1986, Voto et al 1990, Chan et al 1997, Jones and Weiner 1999, Bochang et al 2005, Schmittenbecher 2005). This higher rate of re-displacement might be explained by our strict malunion criteria, the prospective follow-up with scheduled radiographs, our test for stability, and the type of cast (non-circumferential cast applied directly after reduction).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Previous studies have found a re-displacement rate of 7–27% in non-operatively treated forearm fractures, whereas we found a rate of 34% (Monga et al 2010, Kay et al 1986, Voto et al 1990, Chan et al 1997, Jones and Weiner 1999, Bochang et al 2005, Schmittenbecher 2005). This higher rate of re-displacement might be explained by our strict malunion criteria, the prospective follow-up with scheduled radiographs, our test for stability, and the type of cast (non-circumferential cast applied directly after reduction).…”
Section: Discussioncontrasting
confidence: 87%
“…Using the grading system (Daruwalla 1979), we found that 21% (AEC) and 33% (AEC and BEC) had excellent results, whereas other authors have found excellent results in 44–100% of such children (Daruwalla 1979, Kay et al 1986, Price et al 1990, Jones and Weiner 1999, Bochang et al 2005, Boero et al 2007). The modified grading system (Price et al 1990) resulted in 33% and 48% excellent results in our 2 groups, as compared to 82% in another study (Price et al 1990).…”
Section: Discussionmentioning
confidence: 69%
“…Forearm fractures represent one of the most common fractures in children aside from clavicle fractures [1][2][3], and the distal radius is the most common fracture site accounting for 20-30% of these fractures [4][5][6][7][8]. Metaphyseal fractures are more common than fractures of the diaphysis, followed by epiphyseal fractures [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining acceptable reduction is not always possible and re-displacement or re-angulation during cast treatment may occur; this is the most commonly reported complication in paediatric forearm fractures [2,[11][12][13]. Very high rates of unacceptable degrees of displacement after the initial fracture reduction have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…One such paper showed excellent results with no displacements when the elbow was immobilised in an extended position and a 17.6% redisplacement with the elbow immobilised in a flexed position [2].…”
Section: Discussionmentioning
confidence: 99%